Inter-individual variability in performance benefits from repeated sprint training in hypoxia and associated training parameters - Takei, Naoya; Muraki, Ryuji; Girard, Olivier; Hatta, Hideo (Frontiers in Sports and Active Living, 2025)
This study examined whether inter-individual variability exists in repeated sprint training in hypoxia (RSH) and how peripheral oxygen saturation (SpO2) affects physiological demands and mechanical output, and subsequent training outcomes. Sixteen highly-trained sprint runners completed six sessions of RSH consisting of two sets of 5 × 10-s all-out sprints (fraction of inspired oxygen: 0.15), with pre- and post-tests involving 10 × 10-s all-out sprints in normoxia. Average SpO2, training impulse (TRIMP), and relative total work (relative TW; standardized by pre-test TW) during training sessions were calculated. After the intervention, MPO increased by +3.8% (P = 0.001) and sprint decrement score by +6.0% (P = 0.047). However, inter-individual variability in performance improvement observed and nearly 20% of participants did not obtain performance benefit. Average SpO2 during training sessions correlated significantly with relative TW (r = 0.435, P = 0.008), indicating that participants with higher SpO2 performed more work during training. Relative TW was strongly correlated with performance improvement (r = 0.833, P < 0.001), suggesting that those who produced more work during training experienced greater performance gains. TRIMP showed no significant correlation with SpO2 or performance improvement. In summary, greater peripheral deoxygenation leads to lower mechanical work and consequently smaller performance improvement following RSH. The variability in peripheral deoxygenation and relative TW among highly-trained sprint runners may contribute to the heterogeneous training effects observed.